In silico phosphorylation-independent activation of arrestin-3 protein by means of small molecules - Kurt, Mehmet Hanifi (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2019)
G protein-coupled receptors (GPCRs) are responsible for communication of the cell with its surroundings. Upon ligand binding, a set of conformational changes occurs at the GPCR, which triggers activation and dissociation of G protein from the receptor. Subsequently, the receptor is phosphorylated, and activated/phosphorylated receptor causes recruitment of Arrestin to terminate signaling. Arrestin family is composed of four proteins, namely, Arrestin(Arr)-1, 2, 3 and 4. In spite of sharing a high structural similarity and conserved structural fold, the members display remarkable differences in their preference for receptor phosphorylation. Specifically, Arr-1/Arr-4 can exclusively bind to activated/phosphorylated Rhodopsin, whereas Arr-2/Arr-3 can bind to various types of GPCRs. Moreover, Arr-3 can also bind to non-phosphorylated receptors depending on the type of the receptor. The phosphorylation-independent activation mechanism remains elusive; but, might be utilized for the treatment of crucial diseases such as congestive heart failure. Until now, phosphorylation-independent Arrs have been attempted to be created but ended up with problems like instability of the protein. In this thesis project, we aim to activate Arr-3 in silico by means of small molecules. To do so, we target key regions, which are involved in the activation mechanism, on Arr-3 using small molecules that are retrieved from the ZINC database. Our results show that small-molecule/Arrestin complexes are stable and the rotation angle, which is required for activation, is achieved. Therefore, this study provides a framework for the development of phosphorylation-independent Arr-3 and also an insight into the molecular mechanism of non-classical phosphorylation-independent activation mechanism.

G protein-kenetli reseptörler (GPKR) hücre ve hücre çevresi iletişiminden sorumludur. Ligand bağlanmasını takiben GPKR'de, G proteinin aktivasyonuna ve reseptörden ayrılmasına neden olan bir dizi konformasyonel değişiklik meydana gelir. Daha sonra reseptör fosforile edilir ve aktif/fosforile edilmiş reseptör Arrestin alımına, sinyalin sonlandırılmasına neden olur. Arrestin protein ailesi, Arrestin(Arr) -1, 2, 3 ve 4'ten, yani dört proteinden oluşur. Bu ailenin üyeleri, yüksek yapısal benzerliklerlerine ve korunmuş yapısal katlanmalarına rağmen, reseptör forforilasyon tercihlerinde dikkate değer farklılıklar göstermektedir. Özellikle, Arr-1/Arr-4 sadece aktive edilmiş/fosforlanmış Rhodopsin'e bağlanabilirken, Arr-2/Arr-3 çeşitli GPKR tiplerine bağlanabilir. Ayrıca, Arr-3 reseptörün tipine bağlı olarak fosforile edilmemiş reseptörlere de bağlanabilir. Fosforilasyondan bağımsız aktivasyon mekanizması henüz tam olarak anlaşılmasa da; konjestif kalp yetmezliği gibi önemli hastalıkların tedavisinde kullanılabilir. Şimdiye kadar fosforilasyondan bağımsız Arrestinler yaratılmaya çalışılmıştır, ancak bu yöntem proteinin kararsızlığı gibi sorunlara neden olmuştur. Bu tez projesinde, Arr-3'ü in siliko'da küçük moleküller ile aktif hale getirmeyi amaçlıyoruz. Bunu yapmak için, ZINC veritabanından alınan küçük molekülleri kullanarak, Arr-3'ün aktivasyon mekanizmasına dahil olan kilit bölgelerini hedefliyoruz. Sonuçlarımız, küçük moleküllü Arrestin komplekslerinin stabil olduğunu ve aktivasyon için gerekli olan dönme açısının elde edildiğini göstermektedir. Dolayısıyla bu çalışma, fosforilasyondan bağımsız Arr-3'ü geliştirmek ve klasik olmayan aktivasyon mekanizmasının moleküler mekanizmasını anlamak için kullanılabilecek bir bakış açısı sağlamaktadır.
Arrestin-3 proteininin In siliko'da küçük moleküller yardımıyla fosforilasyondan bağımsız olarak aktivasyonu